2018
DOI: 10.1001/jamafacial.2017.2423
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Cosmetic Augmentation of the Nasal Tip and Nasal Dorsum With Expanded Polytetrafluoroethylene

Abstract: IMPORTANCE Expanded polytetrafluoroethylene (ePTFE) is a widely used alloplast, but studies of augmentation of the nasal tip and nasal dorsum with ePTFE are lacking. OBJECTIVE To investigate whether attaching the conchal cartilage as shield grafts at the distal end of the graft can prevent extrusion and whether the use of ePTFE in the nasal tip can achieve a stable aesthetic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Nearly 80% of patients who sued their surgeon after rhinoplasty did so due to poor perceived cosmetic outcomes, and almost 40% because of functional problems postoperatively, according to a 2011 published study. 4 Although there are literature describing complication rates and perioperative risk factors, 1,[5][6][7][8][9][10][11][12][13] there remains a paucity of data connecting these real complications to the theoretical risks described during the rhinoplasty consent process. The relationship between what is routinely discussed during the informed consent process and actually documented complication rates is unknown for rhinoplasty, and correlations have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 80% of patients who sued their surgeon after rhinoplasty did so due to poor perceived cosmetic outcomes, and almost 40% because of functional problems postoperatively, according to a 2011 published study. 4 Although there are literature describing complication rates and perioperative risk factors, 1,[5][6][7][8][9][10][11][12][13] there remains a paucity of data connecting these real complications to the theoretical risks described during the rhinoplasty consent process. The relationship between what is routinely discussed during the informed consent process and actually documented complication rates is unknown for rhinoplasty, and correlations have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…The overall warping rate as reported by fifteen studies (530 participants) was 1.6% (95% CI 0.5%−2.6%). Four studies 16 , 24 , 35 , 36 used alloplastic grafts and reported a prevalence rate of 1.6% (95% CI −0.5% to 3.7%), while in the autogenic group, the pooled proportion of warping as reported by ten studies 18 , 19 , 20 , 21 , 23 , 28 , 33 , 37 , 38 , 39 was 1.5% (95% CI 0.3%−2.8%) ( Fig. 4 ).…”
Section: Resultsmentioning
confidence: 98%
“…After implanting the ePTFE material, an histological observation showed that there was more tissue cells and giant cells on the surface of the material, the pores of the material were filled with a collagen matrix, the fibroblasts and functional capillaries attached to the surface of the material, and the tissue adheres to the surface of the material and grows in the pores of the material. Although the microporous structure of the material is firmly integrated into the tissue, it does not form a fibrous cystic structure and can be completely removed [ 43 ]. Good biocompatibility.…”
Section: Classification Of Plastic Cosmetic Materialsmentioning
confidence: 99%
“… Good biocompatibility. The ePTFE material has good biocompatibility, only a slight tissue reaction such as skin redness of the implant site [ 41 ], and good soft tissue stability [ 43 , 44 ]. Good physical properties.…”
Section: Classification Of Plastic Cosmetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation